A Review of Ethno-STEM Learning Modules in Chemical Kinetics: Bridging Cultural Relevance and Conceptual Understanding of Reaction Rates - Selviana Musa; Akram La Kilo; Ishak Isa; Masrid Pikoli (Universitas Negeri Gorontalo, 2026)
This review explored how ethno-STEM learning modules help students understand reaction rates in chemical kinetics. These modules combine science with culture to make lessons more engaging and easier to relate to. We looked at how the modules were designed and used, how they supported learning, and how they mixed cultural content with science. We also compared different strategies—like inquiry learning and technology use—and identified common teaching problems.We focused on studies from secondary schools, vocational programs, and universities published up to mid-2024. These studies used different methods, such as interviews, surveys, and classroom experiments. We found that culture-based modules made chemistry more relevant and kept students motivated. Inquiry learning and technology also helped students understand reaction rates better. However, many of these strategies still need better ways to measure success and reach more students. Some students struggled with graphs and formulas, but active learning and visual tools helped improve their understanding. Teachers and students liked the modules because they connected chemistry to real life and local knowledge. Still, how engagement is measured varies between studies. In general, this review shows that ethno-STEM has strong potential to improve chemistry lessons by linking science and culture. But future research should be more consistent and explore how to use these methods in different types of classrooms.